2019
DOI: 10.4269/ajtmh.19-0175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Adverse Events from a Standardized Multidrug-Resistant Tuberculosis Regimen in a Rural Setting in Angola

Abstract: Treatment for multidrug-resistant tuberculosis (MDR TB) is associated with adverse events (AE). Patients treated with an MDR TB regimen in Hospital Nossa Senhora da Paz, Cubal, Angola, were prospectively enrolled from May 2013 to July 2015. Baseline characteristics, AE, and clinical and microbiological outcomes were recorded. A total of 216 patients were treated with an MDR TB regimen and 179 (82.9%) patients developed at least one AE. The most common AE were elevation of liver enzymes (46.8% of patients), ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Study periods ranged from 2005 to 2020 (Ngabonziza et al, 2020, Sifna et al). Eleven studies were retrospective cohort studies (Akinsola et al, 2018, Bakare et al, 2021, Bulabula et al, 2019, Ciza et al, 2020, Ige and Oladokun, 2018, Kamara et al, 2022, Ngabonziza et al, 2020, Sifna et al, Souleymane et al, 2021 and three were prospective (Aznar et al, 2019, Kuaban et al, 2015, Schwoebel et al, 2020. The mean study population size was 304.9 (range 115-845), most patients were males (range 51.3-84.1%) (Kuaban et al, 2015, Souleymane et al, 2021 while the median age ranged from 28 to 35 years (Bulabula et al, 2019, Kamara et al, 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study periods ranged from 2005 to 2020 (Ngabonziza et al, 2020, Sifna et al). Eleven studies were retrospective cohort studies (Akinsola et al, 2018, Bakare et al, 2021, Bulabula et al, 2019, Ciza et al, 2020, Ige and Oladokun, 2018, Kamara et al, 2022, Ngabonziza et al, 2020, Sifna et al, Souleymane et al, 2021 and three were prospective (Aznar et al, 2019, Kuaban et al, 2015, Schwoebel et al, 2020. The mean study population size was 304.9 (range 115-845), most patients were males (range 51.3-84.1%) (Kuaban et al, 2015, Souleymane et al, 2021 while the median age ranged from 28 to 35 years (Bulabula et al, 2019, Kamara et al, 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Two additional articles were obtained from other sources (Kamara et al, 2022, Sifna et al). Of the remaining articles, 14 were included for quantitative analysis (Akinsola et al, 2018, Aznar et al, 2019, Bakare et al, 2021, Bulabula et al, 2019, Ciza et al, 2020, Ige and Oladokun, 2018, Kamara et al, 2022, Kuaban et al, 2015, Ngabonziza et al, 2020, Schwoebel et al, 2020, Sifna et al, Souleymane et al, 2021. Several articles contained overlapping data and were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant proportion of TB patients undergoing treatment with aminoglycosides develop ototoxicity [6,42,43]. Studies suggested that ototoxicity is more frequent in resource-limited settings than in developed nations [39].…”
Section: Protective Effects Of Nac Against Ototoxicitymentioning
confidence: 99%